2000
DOI: 10.1038/sj.bmt.1702429
|View full text |Cite
|
Sign up to set email alerts
|

Non-infectious lung complications are closely associated with chronic graft-versus-host disease: a single center study of incidence, risk factors and outcome

Abstract: Summary:Non-infectious lung complications (NILC) are frequent, influencing morbidity and mortality of patients after allogeneic BMT. Although the term NILC encompasses a number of different entities, an association with GVHD has been noted for almost all of them. Our study was directed towards assessing the incidence and risk factors for developing NILC, as well as the response to treatment and long-term outcome. Forty (14.7%) out of 272 patients surviving for more than 3 months after allogeneic BMT, developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 26 publications
(31 reference statements)
1
60
1
Order By: Relevance
“…The latter limitation adds to the call made by others to improve routine data collection in BMT patients for use in future investigations. 14 In summary, in a large group of patients who received BMT, we observed that approximately 6% had a major decrease in the FEV1/FVC ratio consistent with the onset of OB. Patients with OB almost universally had predating cGVHD and had greater mortality.…”
Section: Discussionmentioning
confidence: 87%
“…The latter limitation adds to the call made by others to improve routine data collection in BMT patients for use in future investigations. 14 In summary, in a large group of patients who received BMT, we observed that approximately 6% had a major decrease in the FEV1/FVC ratio consistent with the onset of OB. Patients with OB almost universally had predating cGVHD and had greater mortality.…”
Section: Discussionmentioning
confidence: 87%
“…[1][2][3][4][5] We recently proposed a clinicopathologic categorization of DLD as subacute cellular interstitial pneumonia, bronchiolitis obliterans and acute lung injury. We also demonstrated these entities to be heterogeneous in regard to variables such as predominant pattern of lung involvement (airway or parenchyma), onset and clinical behaviour (acute, subacute, or chronic) and response to immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The pathogenesis is still a matter of debate, although a key role for immunopathologic mechanisms related to chronic graft-versus-host disease (c-GVHD) has been strongly suggested by the identification of c-GVHD in sites other than the lung as a risk factor and by the satisfactory response to the immunosuppressive therapy observed in several previous studies. [1][2][3][4][5] However, a temporally unified view of the ongoing morphologic reactions taking place in this setting remains an enigma to us since no longitudinal biopsy results have been available until now.…”
mentioning
confidence: 99%
“…8,9 The incidence of LONIPCs is 10-25% and they are closely associated with TRM. 8,10,11 The pathogenesis of LONIPCs has not been elucidated, but their development is consistently associated with the presence of chronic GVHD, [10][11][12][13][14][15][16] indicating that allo-immune reactions play a major role in the development of LONIPCs.…”
Section: Introductionmentioning
confidence: 99%